Group randomized trial of teaching tobacco-cessation counseling to senior medical students: a peer role-play module versus a standardized patient module - Park, Kye-Yeung (BMC Med Educ, 2019)
BACKGROUND: An important barrier to smoking-cessation counseling for physicians is a lack of education at the undergraduate level. Interactive methods such as peer role-play (RP) or modules utilizing standardized patients (SPs) may be effective for medical students to enhance their performance on tobacco cessation counseling. This study compared the effectiveness of a module using SPs to that of a RP module for undergraduate medical students on tobacco cessation counseling. METHODS: This study was conducted over a single week of the family medicine clerkship. One hundred and thirteen fourth-year medical students were randomized into either the SP group or the RP group. A RP module involved a ten-minute encounter between the student doctor and the student patient followed by five minutes of feedback from the observer student using a group developed checklist. In a SP module, each student was asked to interview a SP portraying a smoker with willingness to quit. After the encounter, the SP provided five minutes of direct oral feedback to the student. In both modules, the total intervention lasted three-and-half hours and was supervised by faculty staff. Students’ objective structured clinical examination (OSCE) scores were evaluated to determine their tobacco cessation counseling skills. Four evaluation periods were conducted at baseline, postintervention, post-clerkship, and before receiving the Korean medical licensing examination (KMLE). Students’ smoking knowledge test scores and counseling self-confidence levels at pre- and post-intervention were also compared. RESULTS: In both groups, post-intervention OSCE scores increased significantly compared to baseline (Cohen’s d 0.87, p < 0.001 in SP group; d 0.77, p < 0.001 in RP group). However, there were no differences between the two groups. Students achieved the highest OSCE score for smoking-cessation counseling before the KMLE. After training, student self-confidence and smoking-knowledge test scores increased significantly, regardless of the type of module. Self-confidence was higher in the SP group compared with the RP group (d 0.37, p = 0.01). CONCLUSIONS: Peer role-play may be equivalent to the SP method with regard to knowledge and skills reported during smoking-cessation counseling and SP method may be better in self-confidence. Cost and student self-confidence may be important factors when choosing among the teaching methods for smoking-cessation counseling.